2002
DOI: 10.4049/jimmunol.169.9.5130
|View full text |Cite
|
Sign up to set email alerts
|

Ly-6 Superfamily Members Ly-6A/E, Ly-6C, and Ly-6I Recognize Two Potential Ligands Expressed by B Lymphocytes

Abstract: Most hemopoietic cells express one or more members of the Ly-6 supergene family of small glycosylphosphatidylinositol-linked proteins. Although levels of Ly-6 proteins vary with stages of differentiation and activation, their function largely remains unknown. To ascertain whether ligands for Ly-6 proteins exist, chimeric proteins were constructed in which Ly-6E, Ly-6C, and Ly-6I were fused to the murine IgM heavy chain. These chimeras specifically stained both developing and mature B lymphocytes, as assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 61 publications
(44 reference statements)
0
27
0
1
Order By: Relevance
“…Ligands for LY6 molecules, including LY6A, have been described on the lymphoid cells; however, the identification of such ligands is controversial (52)(53)(54)(55). Furthermore, ligands have not been wholly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Ligands for LY6 molecules, including LY6A, have been described on the lymphoid cells; however, the identification of such ligands is controversial (52)(53)(54)(55). Furthermore, ligands have not been wholly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Following the fate of adoptively transferred, purified monocyte subsets revealed that lesional macrophages derived predominantly from circulating Ly-6C hi monocytes, pointing to an active role in this process for the membrane-bound, glycosylphosphatidylinositol-linked protein Ly-6C (44)(45)(46). Future studies will show whether Ly-6C serves only as a marker for or also contributes functionally to inflammatory monocytes, whether Ly-6C characterizes inflammatory cells capable of tissue transmigration, and whether therapeutic targeting of Ly-6C, or a human equivalent, contains monocytosis and consequently reduces atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sca-1 induces lymphocyte proliferation [32]; in the case of C. carpio, FALC cells probably act as engagers, leading to the fusion of this biomolecule with the IgM heavy chain of this fish species, as documented in mammals B lymphocytes [52]. In addition, Sca-1 causes the co-regulation of a variety of different signalling pathways that are able to modify the signalling capacity of the receptor complex [32]; in the case of C. carpio, FALC cells favour a Th2-type response.…”
Section: Discussionmentioning
confidence: 97%